Role of the Purkinje-Muscle Junction on the Ventricular Repolarization Heterogeneity in the Healthy and Ischemic Ovine Ventricular Myocardium - Martinez, Marine E.; Walton, Richard D.; Bayer, Jason D.; Haïssaguerre, Michel; Vigmond, Edward J.; Hocini, Mélèze; Bernus, Olivier (Frontiers in Physiology, 2018)
Alteration of action potential duration (APD) heterogeneity contributes to arrhythmogenesis. Purkinje-muscle junctions (PMJ) present differential electrophysiological properties including longer APD. The goal of this study was to determine if Purkinje-related or myocardial focal activation modulates ventricular repolarization differentially in healthy and ischemic myocardium. Simultaneous epicardial (EPI) and endocardial (ENDO) optical mapping was performed on sheep left ventricle (LV) wedges with intact free-running Purkinje network (N=7). Preparations were paced on either ENDO or EPI surfaces, or the free-running Purkinje fibers (PF), mimicking normal activation. EPI and ENDO APDs were assessed for each pacing configuration, before and after (7 min) of the onset of no-flow ischemia. Experiments were supported by simulations. In control conditions, maximal APD was found at endocardial Purkinje-muscle junction (PMJ) sites. We observed a significant transmural APD gradient for PF pacing with PMJ APD=347±41 ms and EPI APD=273±36 ms (p<0.001). A similar transmural gradient was observed when pacing ENDO (49±31 ms; p=0.005). However, the gradient was reduced when pacing EPI (37±20 ms; p=0.005). Global dispersion of repolarization was the most pronounced for EPI pacing. In ischemia, both ENDO and EPI APD were reduced (p=0.005) and the transmural APD gradient (109±55 ms) was increased when pacing ENDO compared to control or when pacing EPI (p<0.05). APD maxima remained localized at functional PMJs during ischemia. Local repolarization dispersion was significantly higher at the PMJ than at other sites. The results were consistent with simulations. We found that the activation sequence modulates repolarization heterogeneity in the ischemic sheep LV. PMJs remain active following ischemia and exert significant influence on local repolarization patterns.